2016
DOI: 10.1016/j.freeradbiomed.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

MnTE-2-PyP reduces prostate cancer growth and metastasis by suppressing p300 activity and p300/HIF-1/CREB binding to the promoter region of the PAI-1 gene

Abstract: To improve radiation therapy-induced quality of life impairments for prostate cancer patients, the development of radio-protectors is needed. Our previous work has demonstrated that MnTE-2-PyP significantly protects urogenital tissues from radiation-induced damage. So, in order for MnTE-2-PyP to be used clinically as a radio-protector, it is fully necessary to explore the effect of MnTE-2-PyP on human prostate cancer progression. MnTE-2-PyP inhibited prostate cancer growth in the presence and absence of radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 40 publications
2
47
0
1
Order By: Relevance
“…We have previously published that MnTE-2-PyP suppresses PAI-1 expression regulated by the p300/HIF-1β and/or CREB complex with or without 20 Gy irradiation [13]. Because we wanted to determine changes right after irradiation, we used a radiation dose of 20 Gy to aid in observing larger differences between the unirradiated and irradiated cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously published that MnTE-2-PyP suppresses PAI-1 expression regulated by the p300/HIF-1β and/or CREB complex with or without 20 Gy irradiation [13]. Because we wanted to determine changes right after irradiation, we used a radiation dose of 20 Gy to aid in observing larger differences between the unirradiated and irradiated cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have also previously shown that MnTE-2-PyP reduces p300 binding to the HRE binding site on the PAI-1 promoter [13]. We performed a p300 ChIP-qPCR assay to test the binding of the p300 complex to the identified PAI-1 gene promoter region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manganese porphyrins have been shown to inhibit HIF-1β and NF-κB, two pathways that tumors exploit to promote survival and progression of the cancer cell [47, 51, 52]. Therefore, one explanation for how MnTnBuOE-2-PyP may be inhibiting cancer growth is through the inhibition of these two pathways.…”
Section: Discussionmentioning
confidence: 99%